Gender determination from maxillary sinus using computed tomography scans - A radiographic study - Jaideepa; Ashutosh Jha; Dhaval N Mehta; Vasundhara Singh; Kanchan Malawat; Shalini Sinha (Wolters Kluwer Medknow Publications, 2023)
Aims and Objective: Purpose of this research was to check the precision of gender identification using computed tomography (CT) head and neck scans and volumetric analysis of the maxillary sinus. Materials and Methods: For 50 patients (25 females and 25 males), left and right maxillary sinus scans were acquired, and linear measurements (width, length, height, and volume) were assessed. Both maxillary sinus measurements' means and standard deviations were computed and contrasted. Results: Males have been found to have considerably larger maxillary sinuses than females. Conclusion: Accurate gender determination is possible with the use of maxillary sinus.